Epidermodysplasia Verruciformis–like HPV Infection of the Vulva in Immunosuppressed Women. (May 2018) - Pohthipornthawat, Natkrita; Feldman, Sarah; Granter, Scott R.; Laga, Alvaro C.; Crum, Christopher P.; Herfs, Michael
Abstract : The vast majority of vulvar human papilloma virus infections are produced by α human papilloma viruses and consist of exophytic or flat warts and classic or "usual" vulvar intraepithelial neoplasia. This report details 2 examples of epidermodysplasia verruciformis–like lesions of the vulva in women who were immunosuppressed. The most consistent morphologic feature was the presence of abnormal mature keratinocytes with large pale open nuclei with small nucleoli and eosinophilic cytoplasm, situated in the upper epithelial layers. In addition to these features, which are commonly seen in epidermodysplasia verruciformis-associated lesions, 1 case displayed in addition more extensively distributed abnormal nuclei, including involvement of both the upper epithelial strata and the epithelial/stromal interface. Both lesions were associated with β-papilloma virus type 5. The unique aspects of epidermodysplasia verruciformis-like lesions relative to the more common human papilloma virus infections of the vulva are highlighted and these cases illustrate the range of epithelial distribution that might be encountered in lesions involving the vulvar mucosa.